Diurnal variation in Uchikomi fitness test performance: Influence of warm-up protocols - Eken, Özgür; Yagin, Fatma Hilal; Eken, Ismihan; Gabrys, Tomasz; Knappova, Vera; Bayrakdaroglu, Serdar; Akyildiz, Zeki; Nobari, Hadi (Frontiers in Psychology, 2022)
Performance is judged using a variety of methods to ensure uniformity between competitions. Uchikomi Fitness Test (UFT) could accomplished between morning qualifying and evening finals. The purpose of this study is to investigate the impact of different warm-up protocols on UFT at different times of the day in female judokas. Ten volunteer women who had been practising judo on a regular basis for more than 5 years and actively competed in international tournaments took part in this study. Judokas completed UFT, either after no-warm-up (NWU), specific warm-up (SWU), and linear+lateral warm-up (FWU) protocols for two times a day in the morning: 09:00–11:00 and in the evening: 16:00–18:00, on non-consecutive days. In conclusion, there was a significant increase in UFT scores (F = 9.89; p = 0.002), a + b (F = 4.42; p = 0.04) and heart rate (F = 28.99; p < 0.001) in the early evening compared to the morning. Increases in UFT performance were observed in the SWU protocol compared to the NWU and FWU protocols (p < 0.05). However, the interaction between time of day and warm protocol was not significant (p > 0.05). The UFT performance revealed diurnal variation, and the judokas’ performances may be favourably affected more in the late hours, particularly following SWU procedures.